Digital fortress - Brown, Dan, 1964-; Corgi Book. (London : Corgi Book, 2004)
Cryptographer Susan Fletcher finds herself fighting for her country, her life, and the life of the man she loves when she is called in by the National Security Agency to decipher a mysterious code and discovers a plot that has the power to cripple U.S. intelligence.
Adult
Keywords: United States. -- National Security Agency -- Fiction; Code and cipher stories; Cryptographers -- Fiction